2014
DOI: 10.1039/c4cc05062b
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical evidence that electrostatics governs easy-axis orientation in DyIII-based molecular chains

Abstract: Magnetic slow relaxation is observed in a Dy(III)-based molecular chain and the magnetic easy-axis is determined via single-crystal magnetometry. Ab initio calculations confirm its orientation and highlight that the latter is governed neither by coordination polyhedron symmetry nor by the chain direction but rather by the single-ion electrostatic environment, a feature that is confirmed by a similar theoretical analysis on other Dy(III) chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 24 publications
(6 reference statements)
2
28
0
Order By: Relevance
“…The substitution of the ancillary ligand does not have any significant influence on the orientation of the easy magnetic axes (Figure ); despite the different symmetry of the coordination environment, the easy magnetic axes are oriented almost strictly perpendicular to the Dy–Dy direction (calculated angles are 88.46° and 89.96° for Dy and DyPyNO , respectively). This agrees with the results of studies of similar compounds where easy magnetic‐axis orientation is not guided by coordination polyhedron symmetry but rather by global electrostatic considerations in the molecule , , , …”
Section: Resultssupporting
confidence: 89%
“…The substitution of the ancillary ligand does not have any significant influence on the orientation of the easy magnetic axes (Figure ); despite the different symmetry of the coordination environment, the easy magnetic axes are oriented almost strictly perpendicular to the Dy–Dy direction (calculated angles are 88.46° and 89.96° for Dy and DyPyNO , respectively). This agrees with the results of studies of similar compounds where easy magnetic‐axis orientation is not guided by coordination polyhedron symmetry but rather by global electrostatic considerations in the molecule , , , …”
Section: Resultssupporting
confidence: 89%
“…All coordinated oxygen atoms have been considered explicitly. In fact, some of us have previously demonstrated that a too‐simplified description of the neighboring environment of a given Dy III in a Dy chain can lead to a wrong description of the electrostatic features of the compound . This system can be then considered as a good model of the doped compound Y:Dy .…”
Section: Resultsmentioning
confidence: 99%
“…[10,[18][19][20][21][22] Single-crystal magnetic measurements are still not very widespread, [23,24] even though they can cast light on magnetic anisotropy by providing access to the preferred orientations of magnetisation and to the degree of axiality of the low-lyingl evelso ft he J multiplet. [25][26][27] However,m ost crystal structures are comprised of symmetry-related but magnetically non-equivalent sites. In these cases, single-crystal magnetometry provides an averaged responsea nd deconvolution of the different contributions to anisotropy is often impossible.…”
Section: Introductionmentioning
confidence: 99%